Incidence of HBV Reactivation in Psoriasis Patients Undergoing Cytokine Inhibitor Therapy: A Single-Center Study and Systematic Review with a Meta-Analysis - Meng Hsuan Kuo; Ping-Hung Ko; Sz-Tsan Wang; Chih-Wei Tseng (Viruses)
Background: Psoriasis patients who are seropositive for hepatitis B surface antigen (HBsAg) or hepatitis B core antibody (HBcAb) face an elevated risk of hepatitis B virus reactivation (HBVr) when treated with cytokine inhibitors. This study aims to elucidate the risk in this population. Methods: A retrospective chart review was conducted to assess the risk of HBVr in 73 psoriasis patients treated with cytokine inhibitors from 2013 to 2023. Additionally, a systematic review and meta-analysis were performed, pooling data from 10 studies (including our cohort) and adhering to PRISMA guidelines. Statistical heterogeneity was assessed using the I2 statistic, and pooled proportions were calculated using a random effects model. Results: No HBVr cases were observed among the 11 HBsAg+ patients in the cohort. However, two of the sixty-two (3.2%) HBsAg−/HBcAb+ patients experienced reactivation during therapy, with outcomes ranging from spontaneous recovery in one case to death from hepatic failure despite antiviral treatment in the other. The meta-analysis, pooling data from 10 studies, revealed a reactivation rate of 21.2% (95% CI: 9.4–41.0%) in HBsAg+ patients without prophylaxis and 4.4% (95% CI: 2.2–8.7%) in HBsAg−/HBcAb+ patients. Conclusion: Antiviral prophylaxis is essential for HBsAg+ patients receiving cytokine inhibitors, given the high risk of reactivation. Despite the lower risk for HBsAg−/HBcAb+ patients, the potential severity of outcomes demands careful monitoring and timely action.